2007
DOI: 10.1007/s00531-007-0280-1
|View full text |Cite
|
Sign up to set email alerts
|

High heat flow anomalies on an old oceanic plate observed seaward of the Japan Trench

Abstract: Thirty-three new measurements on the seaward slope and outer rise of the Japan Trench along a parallel of 38°45 0 N revealed the existence of high heat flow anomalies on the subducting Pacific plate, where the seafloor age is about 135 m.y. The most prominent anomaly with the highest value of 114 mW/m 2 is associated with a small mound on the outer rise, which was reported to be a kind of mud volcano. On the seaward slope of the trench, heat flow is variable: high (70-90 mW/m 2 ) at some locations and normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…As the line B is close to the data obtained by Yamano et al (2008) along 38 • 45 N ( Fig. 1), we focused mainly on the lines A and C rather than the line B.…”
Section: Heat Flow Measurementsmentioning
confidence: 91%
See 3 more Smart Citations
“…As the line B is close to the data obtained by Yamano et al (2008) along 38 • 45 N ( Fig. 1), we focused mainly on the lines A and C rather than the line B.…”
Section: Heat Flow Measurementsmentioning
confidence: 91%
“…We conducted heat flow measurements in the northern part of the Japan Trench area for further research on the heat flow anomaly on the incoming Pacific plate reported by Yamano et al (2008). Investigation of the extent and the origin of the heat flow anomaly should provide essential information for estimating the thermal structure of the interplate seismogenic zone.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The downhole temperature (T) was calculated using a constant thermal conductivity (TC) of 1.1 W/(m·K) and a surface heat flow (HF) of 45 mW/m 2 as documented in Yamano et al (2008). The calculation is based on the following law:…”
Section: Estimation Of Temperature Profilementioning
confidence: 99%